Sleep disorder in elderly and their association to anxiety, depression and stress - Alam, Muhammad Shamsul; Binni, Subrina Yeasmin; Khan, Muhammad Zillur Rahman; Hossain, Zoha Mohammad Meherwar; Tasmia, Nur Taj Zarin; Tuba, Farah (Bangladesh Journal of Psychiatry, 2019)
Sleep disorders were associated with physical and mental conditions including psychosis, anxiety and mood disorders. Sleep related disorders were found more in the elderly people. The objective of the study was to find the sleep disorders of the elderly and their association with depression, anxiety and stress. It was done from July 2013 to December 2013 among 100 elderly people of both male and female, of various occupation, education and other socio[1]demographic background found in Probin Hitoisy Sangha of Mirpur, Dhaka and in some other areas of Dhaka city. The ages of the elderly people were 55 and above. The sleep condition was assessed by Pittsburgh Sleep Quality Index (PSQI) and depression, anxiety and stress were assessed by Depression Anxiety Stress Scale 21 (DASS 21). The scales were translated into Bangla and along with questions regarding socio-demographic data, these were supplied to the respondents. The data were collected by face-to-face interview. The results showed that 40% respondents were good sleepers and 60% were poor sleepers. Depression was found in 41 (68.3%) poor sleepers and 10 (25.0%) good sleepers, which was statistically significant (p=0.001). Anxiety was found in 48 (80.1%) poor sleepers and 23(57.5%) in good sleepers and it was also statistically significant (p=0.001). Stress was found in 38 (63.4%) poor sleepers and 8 (20%) in good sleepers and was statistically significant (p=0.001). The study showed depression, anxiety and stress were closely associated with sleep disorders. So, it required due attention for assessing physical, mental and all other relevant problems of the elderly people which could explain and treat the condition and bring about their wellbeing. Bang J Psychiatry 2019; 33(1): 11-15